Intensive integrated yoga therapy on lipid profile, body composition, and insulin resistance among Type 2 diabetes mellitus - Ashween Bilagi; Jintu Kurian; Shilpa Bilagi (Wolters Kluwer Medknow Publications, 2022)
Background: Insulin resistance (IR) is a leading cause of the onset of Type 2 diabetes mellitus (T2DM) among overweight and obese individuals irrespective of their age. This study aimed at assessing the impact of 2 weeks of intensive integrated yoga therapy (IIYT) among overweight individuals diagnosed with T2DM identified with higher IR. Methodology: The current single-group longitudinal pre-post study enrolled adults (n = 30) from a residential health-care center, Bengaluru (India), who were subjected to IIYT, comprising practices at physical, emotional, and intellectual levels incorporating āsana (postures), prāṇāyāma (breathing exercise), kriyā (internal cleansing technique), meditation, notional correction, counseling, yogic diet, and devotional sessions. Pre- and postoutcome measures were homeostatic model assessment for IR (HOMA-IR), fasting serum insulin, lipid profile, body composition, and anthropometric measurements. Results: A significant reduction in HOMA-IR (35.69%, p < 0.001), fasting insulin (28%, p < 0.001), fasting glucose (12.3%, p = 0.039), triglycerides (15.43%, p = 0.003), very low-density lipoprotein (15.5%, p = 0.003), body mass index (2.4%, p < 0.001), weight (2.3%, p < 0.001), hip circumference (1.01%, p < 0.001), waist circumference (1.4%, p < 0.001), and body fat percentage (1.8%, p = 0.039) and a significant increase in lean mass percentage (0.95%, p = 0.045) and water percentage (0.99%, p = 0.04) were observed among the subjects. Conclusion: Regular practice of IIYT regulates lipid and anthropometric measures and increases lean body mass, thereby managing IR, among overweight Type 2 diabetes. However, future works might confirm the findings of the present study.